Budget performance evaluation before and during the COVID-19 pandemic - Nia Rosmiati; Rizkianto, Eko (Journal of Economic, Business & Accounting Research, 2024)
The 2020 crisis was caused by a disease outbreak that had an impact on global health and the economy, including Indonesia. As a quick response the government has refocused and reallocated on spending in handling and overcoming the impact of COVID-19, so that Ministries/Institutions must readjust their programs and budgets which affect the organization's performance targets has been established. Previous research where government agencies experienced a decline in performance during the pandemic. However, based on the Performance Report published by LIPI, shows an increase in average performance achievements. This research aims to examine the results of the evaluation analysis of budget performance variables, namely output achievement, budget realization, efficiency and consistency of fund withdrawals for planning for the 2019 and 2020 period with an exploratory approach use case study method. Data was obtained through documentation studies and in-depth interviews through open questions with the program and budget team, financial and budget at the DIPA unit level, and others. LIPI's performance can be achieved due to the policy of shifting the focus of research activities related to handling the coronavirus, changes in research patterns carried out by researchers, changes in business patterns and processes, and changes in the budget management scheme.